Pemanfaatan Basculator dalam Operasional Decanter untuk Menghitung Tonase Oil in Heavy Phase di Pabrik Kelapa Sawit - Azhar Basyir Rantawi (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
The decanter is a equipment at the clarification station used to quote the oil still contained in the sludge, using the centrifugation principle. Processed sludge will be 3 phases, ie light phase, heavy phase and solid. If the decanter performance is not optimal then it will cause the separation process to be imperfect, because the decanter serves to perform the separation. This will cause the oil in heavy phase ex decanter. How much oil in heavy phase ex decanter should be known as accurately as possible, because the oil in heavy phase is used as the performance reference of the decanter. There are several methods that can be used to determine the amount of oil in heavy phase, ie theoretical calculations and using basculator. Theoretical method of calculation can be used when theoretical test conditions are the same as the actual conditions occurring during the research, whereas the basculator is required if the test conditions do not match the actual conditions that occur. The purpose of this research is to know how much oil in heavy phase produced based on calculation by using Basculator in actual. The results showed that the average oil in heavy phase was 3.422 tons or 0.44% to FFB and the average percentage of material actual heavy weight balance was 41%.